HIV prevalence and testing practices among tuberculosis cases in London: a missed opportunity for HIV diagnosis?. Issue 1 (8th December 2009) - Rodger, A J; Story, A; Fox, Z; Hayward, A; ,
Abstract : Background: Universal testing for HIV in patients with tuberculosis (TB) has been advocated for over a decade. The aim of this study was to describe the prevalence and testing practices of HIV in TB centres in London. Methods: A cohort study was undertaken of all patients with TB in Greater London in 2003–4 (n = 1941). Logistic regression was used to assess factors affecting being offered and accepting testing and having a positive HIV result. Results: The overall known prevalence of HIV was 9.9% (193/1941). In those with a test result (including those diagnosed previously) it was 25.6%. Overall, 50.8% of patients aged ⩾20 years without previous testing were offered HIV testing and, of these, 73% accepted. In multivariable analysis, factors associated with being HIV positive were age 20–49 years, black ethnicity and being born overseas. Those with smear-negative disease and with a poor understanding of English were significantly less likely to be offered HIV testing. Factors associated with refusal of an offered test were female gender or age >49 years. HIV status was not associated with smear status, drug resistance or death, but was associated with CNS disease (OR 1.8, 95% CI 1.0 to 3.0, p = 0.003). Conclusions: Nearly half the patients with TB in London in 2003–4 were not offered HIV testing. In those offered testing, uptake was high. Patients in higher risk groups were more likely to be offered testing but, even within the highest risk groups, testing was not universally offered. This represents a missed opportunity for diagnosing HIV in patients with TB in London.